Inovasi Program Pos Pemberdayaan Keluarga Posdaya Asli Pandanwangi - Rofieq, Mochammad; Siswati, Aris; Nugraha, Ginanjar Indra Kusuma (Jurnal ABM Mengabdi, 2024)
The Family Empowerment Post (Posdaya) is a forum for friendship, advocacy, communication, education and an integrated forum for strengthening family functions. This forum is formed from, by and for families and communities. Posdaya membership is voluntary and not associated with any particular political party, ethnicity, or religion. Because Posdaya activities are empowering all family functions, namely Education, Health, Entrepreneurship, Environment, Religion and Culture, therefore innovation is very much needed in carrying out its work program. Posdaya ASLI is one of the Posdayas formed by community groups in the RW. 14 Kelurahan Pandanwangi Kecamatan Blimbing, Malang City. The purpose of this activity is to innovate the empowerment program at Posdaya ASLI, especially the production of Jilbab Syar'i "EL-Yasmine". The method of implementing this activity is carried out in stages: Silaturrahmi with the management, Identification of innovation needs, Brainstorming with members, Comparative study of Posdaya empowerment, Comparative study of program innovation, Administrative System Assistance, and Participation in the Entrepreneur Day event. An important outcome of the innovation carried out at this Posdaya is the production of jilbab syar'i products that have the potential to develop with contemporary models and affordable prices.